2006
DOI: 10.1016/j.addbeh.2005.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use in New York after the terrorist attacks: A study of the effects of psychological trauma on drinking behavior

Abstract: Research has suggested that exposure to psychological trauma is associated with increased abuse of psychoactive substances, particularly alcohol. To assess this, we analyzed alcohol consumption, binge drinking, and alcohol dependence among a random sample of 1681 New York City adults 1 year and 2 years after the September 11 attacks. In multivariate models controlling for demographic factors, other stressor exposures, social psychological resources, and history of anti-social behavior, we found that greater ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 51 publications
(63 reference statements)
9
111
3
2
Order By: Relevance
“…This finding accords with evidence that substance abuse increases following disasters (Boscarino et al, 2006). Previous reports have noted the high rates of alcohol abuse in rural parts of Australia (Australian Institute of Health and Welfare, 2008), and it is probable that the elevated rates in the less affected communities can be explained by this factor.…”
Section: Discussionsupporting
confidence: 88%
“…This finding accords with evidence that substance abuse increases following disasters (Boscarino et al, 2006). Previous reports have noted the high rates of alcohol abuse in rural parts of Australia (Australian Institute of Health and Welfare, 2008), and it is probable that the elevated rates in the less affected communities can be explained by this factor.…”
Section: Discussionsupporting
confidence: 88%
“…Hızlı biçim-de içme davranışı ilk bir yıl sonunda daha fazla iken ikinci yılda azalmıştır. Bu durum TSSB tanısı ile değil fakat olayla karşılaşma ile bağlantı göstermek-tedir (7) . New York'ta yaşayan sosyal çalışmacılarda yapılan bir taramada bu olay nedeniyle hizmet verenlerde ikincil travmatizasyona daha çok rastlanmış (8) , ancak mesleki tükenme (burnout) belirtileri ile bu çalışmalara katılma arasında bağlantı görülmemiştir.…”
Section: Ruhsal Travma Ile İlgili Psikiyatrik Tablolarunclassified
“…------IJADR 1(1) ------80 & Randall, 2003;Morris, Stewart, & Ham, 2005;Schneier et al, 2010;Zimmermann et al, 2003), posttraumatic stress disorder or symptoms (Blume, Resor, Villanueva, & Braddy, 2009;Jacobson et al, 2008;McDevitt-Murphy et al, 2010), physical pain (Lawton & Simpson, 2009;Moos, Brennan, Schutte, & Moos, 2010;Riley & King, 2009), cumulative experience with stressful life events (Aseltine & Gore, 2000;Dawson, Grant, & Ruan, 2005;Lloyd & Turner, 2008), after-effects of military combat (Jacobsen et al, 2008;Šakušić et al, 2009;Wilk et al, 2010), after-effects of disasters and terrorism (Boscarino, Adams, & Galea, 2006;Grieger, Fullerton, Ursano, & Reeves, 2003;Hasin, Keyes, Hatzenbuehler, Aharonovich, & Alderson, 2007), after-effects of childhood trauma (Sarin & NolenHoeksema, 2010;Wilsnack, Wilsnack, Kristjanson, Vogeltanz-Holm, & Harris, 2004;Wu et al, 2010), after-effects of assault and criminal victimization (Kaysen et al, 2007;Ullman, Filipas, Townsend, & Starzynski, 2005;Vaughn et al, 2010) and chronic negative emotions arising for other reasons (Costanzo et al, 2007;Dorfman, Trokel, Lincoln, & Mehta, 2010;Witkiewitz & Villarroel, 2009). Links between chronic stress and chronic drinking patterns are found more consistently than links between acute but time-limited stress and immediate drinking responses (Armeli, Todd, & Mohr, 2005;Helzer, Badger, Searles, Rose, & Mongeon, 2006;Skaff, Finney, & Moos, 1999; but see also …”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%
“…Several studies have found no increase in drinking related to stressful life events (Droomers, Schrijvers, Stronks, Van De Mheen, & Mackenbach, 1999;Robertson, Xu, & Stripling, 2010;Welte & Mirand, 1995), social anxiety (Eggleson, Woolaway-Bickel, & Schmidt, 2004;Ham & Hope, 2006;Tran, Haaga, & Chambless, 1997) and posttraumatic stress disorder (Boscarino et al, 2006;Breslau, Davis, & Schultz, 2003;Najdowski & Ullman, 2009), and there are also studies reporting no drinking increase in people who have suffered pain (Yokoyama et al, 2009), sexual victimization (Testa, Livingston, & Hoffman, 2007) and effects of military combat (Fritch, Mishkind, Reger, & Gahm, 2010). Workrelated stress has a particularly uncertain relationship with drinking; sometimes distressed employees drink more (Ahola et al, 2006;Bobak et al, 2005;Richman, Shinsako, Rospenda, Flaherty, & Freels, 2002) and sometimes they do not (Hodgins, Williams, & Munro, 2009;Kouvonen et al, 2005;Ng & Jeffery, 2003).…”
Section: Ijadr International Journal Of Alcohol and Drug Researchmentioning
confidence: 99%